SCIENTIFIC AND PRACTICAL BASES OF STUDYING THE PROBLEM OF DEVELOPING AUTOPEDAGOGICAL COMPETENCE OF TECHNOLOGICAL EDUCATION TEACHER - Malika Mominovna Parpieva (Web of Journals Publishing, 2023)
In this article, the process of forming the autopedagogical competence of the future teacher of technological education and creative pedagogical individuality has not been sufficiently studied, and the problems of studying the training of personnel based on creative approaches have been analyzed.
Keywords: autopedagogical competence, technological education, anthropological, ontological, dialogical, social pedagogy, sociogenic, psychogenic, acmeological approach, STEAM - method, cognitive-operational.